Landscape of biomolecular condensates in heat stress responses - Londoño Vélez, Violeta; Alquraish, Fatema; Tarbiyyah, Ibrahim; Rafique, Fareena; Mao, Duruo; Chodasiewicz, Monika (Frontiers in Plant Science, 2022)
High temperature is one of the abiotic stresses that plants face and acts as a major constraint on crop production and food security. Plants have evolved several mechanisms to overcome challenging environments and respond to internal and external stimuli. One significant mechanism is the formation of biomolecular condensates driven by liquid–liquid phase separation. Biomolecular condensates have received much attention in the past decade, especially with regard to how plants perceive temperature fluctuations and their involvement in stress response and tolerance. In this review, we compile and discuss examples of plant biomolecular condensates regarding their composition, localization, and functions triggered by exposure to heat. Bioinformatic tools can be exploited to predict heat-induced biomolecular condensates. As the field of biomolecular condensates has emerged in the study of plants, many intriguing questions have arisen that have yet to be solved. Increased knowledge of biomolecular condensates will help in securing crop production and overcoming limitations caused by heat stress.